PENGARUH PERSEPSI MANFAAT, KEMUDAHAN PENGGUNAAN DAN KEAMANAN TERHADAP NIAT MENABUNG PADA PRODUK TABUNGAN EMAS PEGADAIAN - farokha, sita; Alimuddin Rizal Rivai (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research was conducted because of the background that is influenced by theperception of benefits, ease of use, and security for saving on gold pawnshop savingsproducts. The type of data used is primary data obtained directly from the informant byusing a questionnaire. The population used in this study were customers of PTPegadaian Demak Branch as many as 4,707 customers. With the slovin method, asample of 100 customers was obtained. The sampling technique in this study was doneby purposive sampling. The data that has been obtained will be analyzed using multiplelinear regression analysis. The results of this study concluded that the variables ofperception, ease of use and security proved significant and did not have a positive effecton savings in pawnshop gold savings products.